Assessing pedagogical competence of productive teachers in vocational secondary schools: a mixed approach - Setiawan, Dedi; Triyono, Mochamad Bruri; Sukarno, Sukarno; Nurtanto, Muhammad; Majid, Nuur Wachid Abdul; Hamid, Mustofa Abi (Journal of Education and Learning (EduLearn), 2025)
The objective of this study is to evaluate the effectiveness of teachers in implementing pedagogical skills. The present study used a mixed methods approach. The participants in this study consisted of 55 highly effective educators employed in vocational secondary schools. The research data were acquired using effective teacher questionnaires, peer evaluations, observations, and comprehensive interviews. The findings indicated that a majority of highly effective educators possess a strong comprehension of the practical application of pedagogical competence. Nevertheless, a marginal disparity exists between academic knowledge and its practical application in the respective domain. The facilitation and support of teachers in the development of their pedagogic competences is a crucial responsibility of school principals. Effective and well-structured ongoing training is essential to bridge the divide between theoretical concepts and practical application, and to guarantee that educators possess the requisite expertise and understanding to tackle the demands of the current and future educational landscape. Hence, it is imperative to allocate resources towards teacher professional development and ensure the availability of sufficient assets in vocational secondary schools in order to attain educational excellence in Indonesia.